THE EFFECT OF CONSTRUCTIVISM LEARNING ON STUDENT LEARNING OUTCOMES: A META ANALYSIS STUDY - Yul Ifda Tanjung; Irfandi Irfandi; Teguh Febri Sudarma; Lufri Lufri; Asrizal Asrizal; Hardeli Hardeli (ISER (Indonesian Science Education Research), 2023)
Constructivism in learning is a philosophy that holds where the process of forming knowledge in individuals is the result of mental activity supported by the process of learning experience. Many studies have been conducted on the effect of constructivism theory on learning outcomes, but few have quantifies the effect so that it can be analyzed qualitatively. Therefore, Â the purpose of this research was to quantify the effect size of the relationship between constructivism theory and student learning outcomes using meta-analytic research and data analysis techniques with openMEE software. Data was collected from Scopus and Google Scholar for 17 articles published in 2019 till 2022. Based on the analysis, In terms of the effectiveness of constructivism learning theory, an estimated data of 1.548 is obtained which indicates that constructivist theory has great effectiveness in improving student learning outcomes. In addition, the effect size measurement at the primary and secondary levels of education indicates that the student is in high category. This explains why constructivism learning is very well implemented because children at this level are already able to be encouraged to construct their own knowledge which influences their learning outcomes.